Design Theory Explorer (DTExp.V1.0): visual-interactive innovation for basic design principles in interior design education - Md Ajis, Azizah; Md Ajis, Ahmad Fuzi (2025)
The effective teaching of design theory – particularly the identification and application of the basic design principles – remains a pedagogical challenge in interior design curricula. This paper introduces Design Theory Explorer Version 1.0 (DTExp V1.0), an innovative, image-based learning tool designed to enhance students’ understanding of basic design principles through visual engagement, active learning, and reflective practice. The innovation exists in two formats: a mobile application prototype developed using RMAD (Rapid Mobile Application Development), and a manual PowerPoint slide version adaptable for both digital and offline classrooms. DTExp V1.0 allows undergraduate students to interact with curated visual content by analysing real-world design examples and selecting applicable basic design theory principles, e.g., emphasis, contrast, repetition and etc. Key components include gamified image identification tasks, portfolio-based reflection and challenge-based learning modules, together enabling hands-on design theory application. The activity aligns with constructivists learning theory and Models of Visuospatial Cognition, supporting deep engagement with basic design principles. Preliminary classroom implementations suggest increased student motivation, improved retention of theoretical concepts, and strengthened visual literacy. The DTExp V1.0 represents a scalable, accessible, and pedagogically robust approach to bridging the gap between design theory and practical observation, with potential for cross-disciplinary application in interior design, architecture, art, and visual communication programs.